Sleep, physical activity, sedentary behavior, and risk of cataract: a cross-sectional and prospective study from UK Biobank - Yu Peng; Yuzhou Zhang; Ka Wai Kam; Mary Ho; Sunny Au; Xiujuan Zhang; Mandy PH Ng; Patrick Ip; Alvin Young; Chi Pui Pang; Clement C. Tham; Li Jia Chen; et al. (BMC Medicine)
Abstract Background Cataract is a leading cause of visual impairment globally. Although daily behaviors such as sleep, physical activity (PA), and sedentary behavior (SB) have been associated with cataract risk, the evidence remains controversial and uncertain. This study aimed to examine the independent and combined effects of sleep, PA, and SB on cataract risk using data from the UK Biobank. Methods The cross-sectional analyses included 440,645 participants from the UK Biobank with complete data on sleep, PA, and SB. For the longitudinal analyses, a subset of 426,540 participants without cataract at baseline was included. Cataract cases were identified through hospital inpatient records and self-reported data. Baseline data on sleep, PA, and SB were collected via touchscreen questionnaires. Logistic regression and Cox proportional hazards models were used to examine the independent and synergistic associations between sleep, PA, SB, and cataract. Results In the cross-sectional analyses, 440,645 participants were evaluated (54.0% female; mean [SD] age, 56.5 [8.1] years), of whom 14,105 (3.2%) had cataract. Significant associations were found between poor sleep (OR, 1.35; 95% CI, 1.23–1.48), low PA (OR, 1.06; 95% CI, 1.01–1.11), and cataract. Longitudinal analyses included 426,540 participants (53.9% female; mean [SD] age, 56.3 [8.1] years). During a mean follow-up period of 10.8 years, 55,658 incident cataract cases were recorded. Poor sleep (HR, 1.14; 95% CI, 1.08–1.19), low PA (HR, 1.05; 95% CI, 1.02–1.07), and high SB (HR, 1.08; 95% CI, 1.06–1.11) were correlated with increased cataract risk. The combination of poor sleep, low PA, and high SB further elevated the risk, with the highest odds in cross-sectional (OR, 1.73; 95% CI, 1.37–2.15) and prospective (HR, 1.37; 95% CI, 1.21–1.55) analyses. Replacing 1 h/day of SB time with an equal time spent in total PA and sleep was associated with a 1.7% and 2.7% decreased risk of cataract, respectively. Conclusions Poor sleep, low PA, and high SB are independently and jointly associated with an increased risk of cataract. Modifying these behaviors, either individually or in combination, can effectively mitigate the risk of cataract.